BUDAYA ORGANISASI, LINGKUNGAN KERJA DAN KECERDASAN EMOSIONAL DAN PENGARUHNYA PADA KINERJA KARYAWAN - Chrystho Hendrian Bima Dewantara; Endang Sulistiyani; Fatchun Hasyim (Politeknik Negeri Semarang, 2022)
This study aims to analyze the influence of organizational culture, work environment, and emotional intelligence on the employees’ performance of the Business Service Division of PT Telekomunikasi Indonesia Regional IV Semarang. The population and sample in this study were all employees in the Business Service Division. The sampling technique is the census, which all members of the population are sampled. Data analysis methods included validity test, reliability test, classical assumption test, T test, F test, and coefficient of determination with SPSS 25 program. The results of hypothesis verification and discussion showed that organizational culture, work environment, and emotional intelligence have a positive and significant effect on Employees’ Performance. Emotional intelligence has a dominant impact in improving employee performance.